2019
DOI: 10.1055/s-0039-1693413
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Plate Osteosynthesis Using Fracture Reduction Under the Plate without Intraoperative Fluoroscopy to Stabilize Diaphyseal Fractures of the Tibia and Femur in Dogs and Cats

Abstract: Objective The aim of this study was to prospectively evaluate postoperative alignment when using fracture reduction under the plate (FRUP) during a minimally invasive plate osteosynthesis in tibial and femoral fractures, without intraoperative imaging, and report immediate postoperative complications. Materials and Methods After precise plate contouring and preoperative planning, FRUP was obtained with one cortical screw per fragment. Fractures were stabilized with a plate or plate rod. Tibial/femo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(52 citation statements)
references
References 16 publications
1
49
0
2
Order By: Relevance
“…Authors of a recent article describing a veterinary study on tibial and femur fracture repair via MIO without the use of fluoroscopy reported 12% of cases requiring immediate revision surgery because of misplaced pins and malalignment 21 . Our hope is that the SMH would reduce this immediate revision rate by minimizing fragment movement during surgery.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Authors of a recent article describing a veterinary study on tibial and femur fracture repair via MIO without the use of fluoroscopy reported 12% of cases requiring immediate revision surgery because of misplaced pins and malalignment 21 . Our hope is that the SMH would reduce this immediate revision rate by minimizing fragment movement during surgery.…”
Section: Discussionmentioning
confidence: 98%
“…Challenges of MIO include the inability to visualize the fracture ends, changes of the normal anatomic structures secondary to fracture displacement and soft tissue swelling, difficulty and increased time required to overcome muscle contractions countering satisfactory fragment reduction and alignment, the requirement to rely on implant placement based on regional anatomical landmarks remote from the fracture site, reliance on surgical experience, and risk of inadvertent loss of reduction prior to having secured the final implant 11‐14 . Therefore, MIO may increase the risk of inducing iatrogenic limb malalignment or inappropriate implant placement, which could impact clinical outcomes or require additional surgery 3,4,15‐22 . To minimize those potential concerns, specialized and often costly surgical instrumentation may be required.…”
Section: Introductionmentioning
confidence: 99%
“…Not all the cases had a plate molded on the tibia, which may have triggered the high rates of angular deviations in the present study. This is due to the fact that the tibia has a triangular aspect in the proximal portion, making it difficult to align and affix the plate without proper molding, which was highlighted recently by CABASSU et al (2019), who obtained good alignment in the frontal plane of the dogs while performing the molding and reduction of the fracture through the bone plate.…”
Section: Discussionmentioning
confidence: 99%
“…49 Four additional studies have been published regarding outcomes of MIPO tibial fracture stabilizations in small animals. 31,[33][34][35] Guiot and Déjardin published a prospective study evaluating MIPO of tibial fractures in 28 dogs and 8 cats. Reduction and alignment were facilitated by use of a hanging limb technique, normograde intramedullary pin placement, and/or appropriate plate contouring.…”
Section: Tibial Fracturesmentioning
confidence: 99%
“…The cat returned to full function Cabassu prospectively evaluated efficiency of MIPO to stabilize tibial fractures without the use of intraoperative fluoroscopy in 13 dogs and 8 cats. 33 Alignment was assessed intraoperatively by palpation and clinical evaluation of the plane motion of the adjacent joints. 33 Based on postoperative radiographs, 14% of tibial fractures needed immediate revision surgery for improper intramedullary pin placement, intra-articular screw placement, or sagittal malalignment.…”
Section: Tibial Fracturesmentioning
confidence: 99%